The Spanish Civil War in film as a historiographical source: Andalusia in the film La Trinchera Infinita (2019) and the digital reconstruction of an invisible fascism (Tempo e Argumento, 2021)
Since the second half of the twentieth century, digital culture has meant a revulsive in the historian's profession, which has found other channels for the dissemination of his work. This is especially visible in the cinema of the new Netflix era, with a new look that, from microhistory, seeks to approach the great epics of events, focusing on those who suffer them. We will analyze the award-winning Basque-Andalusian film La Trinchera Infinita (2019), centered on the Spanish Civil War (1931-1939), to reflect on the construction of a fictional script based entirely on some real stories, collected in a journalistic book from 1977. The film represents the invisible fascism, in a narration where absence and shadow are just another character. And where, thanks to digital technology, it has managed to articulate a story that transcends the fact of the conflict, speaking, in general, of the fears of the mind, of loneliness, of the risk of self-exclusion of those who look at the world through a hole.Keywords: history; cinema; spanish civil war; literature; war journalism.